Evaluating different surface patterns and software for Digital Image Correlation during loading and unloading conditions of concrete - Kahr Sissel; Ghosh Subha; Sunayana Sushree; Paraskevoulakos Charilaos; Ottosen Lisbeth M. (MATEC Web of Conferences)
Concrete is the second most used material after water, with a significant environmental impact. The most sustainable method to lower this significant impact is to directly reuse the concrete elements from demolished buildings. To implement this, a non-destructive validation method is required to assess the concrete elements’ residual strength, potentially reduced during utilization. The residual strength of a concrete element depends on the stress it has been exposed to. Using Digital Image Correlation (DIC), it is possible to track the residual strength by analyzing the changes in microcracks during the unloading of the elements in the demolition phase. For this to become a reality, the technique must be accessible to the demolition industry. The DIC technique works by capturing images with a high-resolution camera of a high-contrast pattern, tracking the changes in the pattern over time. Specialized software developed for this purpose is needed for analysis. This study compares the results obtained using the commercial software ZEISS and the open-source MATLAB program Ncorr since the industry is interested in a low-cost solution. It also tests whether the inherent contrast of raw concrete surface or a polished concrete surface is sufficient for the contrast needed for the DIC analysis.